Agricultura química na Inglaterra e nos Estados Unidos no século XIX: alguns aspectos dos estudos e trabalhos sobre o guano - Lima, Edson (2015)
The studies on agriculture, both in England and the United States of America, have been essential for the institutionalization of the chemical agriculture in the nineteenth century. Those studies were centered on the cooperation between the researches developed in educational institutions and the ones developed in the work field. By that time, the increase of the soil fertility was a matter that needed to be solved in both countries and the Peruvian guano began to be broadly used, thus, originating uncountable studies involving its composition and efficiency as a fertilizer. This material accomplished great commercial value, leading to its counterfeiting in so many ways. Thereby, releases focusing on farmers, convincing them of the guano s efficiency as a fertilizer and also warning them about the counterfeits and how to recognize them, were published in the mid-nineteenth century. In this context, this present work approaches, especially, the texts from J.C. Nesbit (published in England) and from S. Robinson (published in the USA), which spread the using of guano as a solution for the soil infertility